Evaluation of Iron Concentration of Five Nigerian Shrubs for their Prospective use in the Therapy of Iron Deficiency Anemia (IDA) - Immaculate, Obika Ogochukwu; Bernard, Ochekwu Edache (Journal of Nutrients, 2021)
Medicinal herbs are commonly being used in the treatment of anemia traditionally and Jatropha tanjorensis Ellis & Saroja, Vernonia amygdalina Delile, Manihot esculenta Crantz, Megaskepasma erythrochlamys Lindau, Solanum macrocarpon L. are local shrubs mostly employed. This study aims to analyze the prospective use of some local shrubs in the therapy of Iron Deficiency Anemia. The proximate composition analysis and the iron content in leaves of the shrubs were determined following the methods of the association of official analytical chemists (A.O.A.C). The results obtained for iron concentration show Jatropha tanjorensis 3.11g/kg, Vernonia amygdalina 1.64g/kg, Manihot esculenta 0.57g/kg, Megaskepasma erythrochlamys 1.23g/kg, and Solanum macrocarpon 2.75g/kg. The range of proximate composition as; protein had Megaskepasma erythrochlamys as the lowest value 3.97% and Vernonia amygdalina as the highest value 50.64%, fat & oil content showed Jatropha tanjorensis with the highest value 1.04% and Megaskepasma erythrochlamys having the lowest value 29.77%, Fiber content showed Vernonia amygdalina has the highest value 1.81% and Solanum macrocarpon has the lowest 12.08%, the carbohydrate content showed Megaskepasma erythrochlamys as the lowest value 2.39% and Manihot esculenta as the highest value 21.02%, and the moisture content showed Manihot esculenta has the lowest value 9.98% and Megaskepasma erythrochlamys has the highest value 83.25%. All five plants have great potential for the treatment of iron deficiency anemia.